2021
DOI: 10.1177/23197145211057339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficit Financing on Economic Growth in Bangladesh: Cointegration and VECM Approach

Abstract: Bangladesh has been encountering a budget deficit since 1972 because of a decrease in the source of income. This paper aims to examine the effect of budget deficit financing on economic growth in Bangladesh throughout 1981–2018. Using secondary data, the paper uses the cointegration test, vector error correction mechanism (VECM) and Granger causality test. Johansen’s cointegration test outcomes find that the study variables are cointegrated and subsequently have a long-run nexus among the variables. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…For instance, Ughulu et al, (2023) found that external sources of deficit financing do not affect economic growth, while Alam et al, (2022), observed that foreign sources of deficit financing increased economic performance. On the other hand, Ibukunle & Akuston (2022) and Abubakar (2021) reported that domestic sources of deficit financing enhanced economic growth in Nigeria; Jakpa & Osho-Itsudi (2020), observed that domestic sources of deficit financing did not enhance the Nigerian economy.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ughulu et al, (2023) found that external sources of deficit financing do not affect economic growth, while Alam et al, (2022), observed that foreign sources of deficit financing increased economic performance. On the other hand, Ibukunle & Akuston (2022) and Abubakar (2021) reported that domestic sources of deficit financing enhanced economic growth in Nigeria; Jakpa & Osho-Itsudi (2020), observed that domestic sources of deficit financing did not enhance the Nigerian economy.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Non-bank financing, although not statistically significant, exhibited the right sign as it had a positive effect. Alam et al, (2022) examined the effects of budget deficit financing on economic growth in Bangladesh from 1981 to 2018 using secondary data that were subjected to a co-integration test, vector error correction mechanism (VECM) and Granger causality test. Johansen's cointegration subsequently had a long-run nexus among the variables.…”
Section: Empirical Review Of Literaturementioning
confidence: 99%
“…The findings revealed that external source of financing budget deficit, internal source of financing budget deficit as well as debt servicing has a significant effect on money demand in the Nigerian context. Alam, Sadekin, Islam, and Moudud-Ul-Huq (2021) examined the effect of budget deficit financing on economic growth in Bangladesh throughout 1981-2018. Using secondary data, the paper used the cointegration test, vector error correction mechanism (VECM), and Granger causality test.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Taylor, Proano, Carvalho, and Barbosa (2012) investigated the effects of the primary fiscal deficit on economic growth with VAR which was reported that the more spending and less taxation can positively influenced on the growth of economy of the USA. The rising Asian economy, Bangladesh, adopted deficit budget since 1972 and the recent study with VECM and Granger causality by Alam, Sadekin, Islam, and Moudud-Ul-Huq (2022) conclude that the government domestic debt (GDD) and government external debt (GEXD) affect positively economic growth (RGDP). In a similar vein, the findings of this study, such as those of Navaratnam and Mayandy (2016), showed that the fiscal deficit has a negative influence on economic growth in all of the South Asian nations included in this study, with the exception of Nepal, where the results showed a positive impact.…”
Section: Brief Literature Reviewmentioning
confidence: 99%